Pelatihan Peningkatan Kompetensi dan Inovasi Pembelajaran bagi Guru Pendidikan Agama Islam menuju Guru Profesional - Anam, Saeful; Iskandar, Khusnan (Academia Publication, 2025)
This community service activity aims to improve the competence and innovation of Islamic Education (PAI) teachers in order to develop professional teachers who are adaptable to developments in modern education. The main challenges faced by PAI teachers today are limitations in utilizing learning technology, low innovation in teaching methods, and the need to adapt to the Merdeka Curriculum paradigm, which demands active and student-centered learning. The activity was carried out using a service learning approach, which is a learning-based community service model that integrates academic activities with direct community service. The activity was carried out in five stages: identification of partner needs, program planning, training and mentoring, reflection-evaluation, and follow-up. The participants were seven PAI teachers from partner schools who took part in a series of workshops, coaching clinics, and hands-on practice in creating digital technology-based learning media. The results of the activity showed a significant improvement in the pedagogical and professional competencies of teachers, especially in their ability to design interactive media and apply creative learning models such as Project-Based Learning. Teachers became more confident and motivated to innovate in religious education in the classroom. In addition, a community of innovative PAI teachers was formed as a forum for collaboration and continuous professional development. This activity proved that the service-learning approach is effective in connecting academic theory with educational practice in the field. Through this training, PAI teachers were able to transform themselves into reflective, creative, and professional educators, while strengthening the role of universities in empowering the educational community.